Does English really open doors? Social class and English teaching in public primary schools in Mexico. (April 2018) - Sayer, Peter
Abstract: Most countries in Latin America are extending English language education in their public school curricula by beginning earlier and increasing hours of L2 instruction. The reason for this rapid expansion is encapsulated in the common refrain "English opens doors, " which acknowledges the perceived power of global English in affording individuals greater economic and social opportunities. Mexico is a prime example, where English instruction in public education has been expanded from 3 to 13 years. On the surface, the new program represents a broad attempt at acquisition planning that would "level the playing field" by significantly expanding access to learning English among working class Mexicans and opening new doors of economic opportunities. Drawing on critical theorists' examinations of class, education, and social reproduction, the author examines how English instruction differs in classrooms across social class, and asks if English will actually change the equation for working class children. Presenting classroom observation data from an impact study of the pilot phase of the Mexican program in the primary grades, and from interviews with a variety of the stakeholders, the researcher looks at ways that the reality of program implementation does and does not match its aims.